Disability Studies in Education: past, present & future? - David J. Connor; Jan Valle (Universidade Federal do Rio Grande do Sul, 2024)
In this article we: provide a brief overview of the genesis and growth of DSE over the past quarter century; describe ways in which it has impacted the four interconnected realms of theory, research, practice, and policy, providing examples of DSE in action including research within classrooms, teacher education programs, and interdisciplinary developments; and share emerging trends within DSE that inform our hopes for the future. By narrating the conceptualization of DSE, its subsequent trajectory, and discussing interrelated issues it seeks to address, our intention is to provide readers with an overview of its contributions to educational thought and the opportunity to engage in with them.